La ressemblance familiale du somatotype pendant la croissance (2002)
ABSTRAC: We have studied the familial resemblance of Heath-Carter’s anthropometric somatotype in a sample of 1350 siblings from 634 nuclear families from the Biscay province (Basque Country, Spain). Correlations between the different types of siblings for endomorphy, mesomorphy and ectomorphy were computed by maximum-likelihood after standardising the data by a multiple regression according to two different models, taking into account the age, the sex and each somatotype component with respect to the other two (Model 1), several shared socio-familial by the siblings (Model 2). In order to examine the effect of age on correlations, the whole sample was divided in three categories of age whose limits correspond to the prepuberal, puberal and postpuberal periods. For both models, all correlations were statistically significant, being the values for mesomorphy higher than for endomorphy. The sex of siblings influences significatively on mesomorphy correlations but not on the other two components. In general, like-sex siblings have significant resemblances for mesomorphy and ectomorphy, but between sisters correlations was rather low compared with that between brothers for endomorphy. This last component was the most influenced by the age, showing a significant decrease of correlations during the considered growth period.